Upaya Mengatasi Sibling Rivalry melalui Layanan Konseling Kelompok - Turniati, Eli; Nusantoro, Eko (Universitas Negeri Semarang, 2015)
Penelitian ini dilakukan berdasarkan fenomena yang terjadi pada siswa kelas VI SDN Sendangmulyo 02 kecamatan Tembalang kota Semarang yang mengalami sibling rivalry. Tujuan penelitian ini yaitu untuk mengetahui apakah konseling kelompok dapat mengatasi sibling rivalry pada siswa kelas VI SDN Sendangmulyo 02. Jenis penelitian adalah penelitian eksperiment dengan desain penelitian one group pre-test dan pos-test design. Subyek penelitian ini, siswa kelas VI SDN Sendangmulyo 02 yang memiliki tingkat sibling rivalry tinggi yang diperoleh dari hasil DCM dan rekomendasi dari guru kelas yaitu terjaring 10 siswa. Metode pengumpulan data menggunakan skala psikologis berupa skala sibling rivalry. Analisis data menggunakan teknik analisis data deskriptif persentase dan uji wilcoxon. Hasil penelitian menunjukan sibling rivalry siswa sebelum diberi perlakuan berupa konseling kelompok dalam kategori tinggi (75.14%). Setelah diberikan konseling kelompok menunjukkan perbedaan, dilihat dari hasil pos test rata-rata sibling rivalry siswa menurun yaitu berada pada kategori rendah (42,95%). Hal tersebut menunjukan bahwa sibling rivalry dapat diatasi melalui layanan konseling kelompok This research was conducted based on phenomena that occur in grade VI SDN Sendangmulyo 02 Tembalang Semarang who experienced sibling rivalry. The purpose of this research is to find out if counseling groups can overcome sibling rivalry at grade VI SDN Sendangmulyo 02. This type of research is research research design alphabets experiment one group pre test and post test design. The subject of this study, students of class VI SDN Sendangmulyo 02 that has a high level of sibling rivalry that results obtained from DCM and the recommendations of the master class that is netted 10 students. Method of data collection using a scale of psychological scale in the form of sibling rivalry. Data analysis data analysis techniques using a descriptive percentage and wilcoxon test. The research results show the sibling rivalry before students are given preferential treatment in the form of group counseling in high category (75.14%). After being given counseling group showed a difference, judging from the results of the post test average of sibling rivalry students dropping IE is at a low (42,95%) categories. It indicates that the sibling rivalry can be addressed through group counselling service. This research was conducted based on phenomena that occur in grade VI SDN Sendangmulyo 02 Tembalang Semarang who experienced sibling rivalry. The purpose of this research is to find out if counseling groups can overcome sibling rivalry at grade VI SDN Sendangmulyo 02. This type of research is research research design alphabets experiment one group pre test and post test design. The subject of this study, students of class VI SDN Sendangmulyo 02 that has a high level of sibling rivalry that results obtained from DCM and the recommendations of the master class that is netted 10 students. Method of data collection using a scale of psychological scale in the form of sibling rivalry. Data analysis data analysis techniques using a descriptive percentage and wilcoxon test. The research results show the sibling rivalry before students are given preferential treatment in the form of group counseling in high category (75.14%). After being given counseling group showed a difference, judging from the results of the post test average of sibling rivalry students dropping IE is at a low (42,95%) categories. It indicates that the sibling rivalry can be addressed through group counselling service.